Revising the "One-Shot" through Lesson Study: Collaborating with Writing Faculty to Rebuild a Library Instruction Session - Rex, Cathy; Jennings, Eric; Hinnant, Kate; Markgraf, Jill; Kishel, Hans; Watson, Shevaun E. (My University, 2013)
The one-shot library instruction session has long been a mainstay for many information literacy programs. Identifying realistic learning goals, integrating active learning techniques, and conducting meaningful assessment for a single lesson all present challenges. Librarians and English faculty at one college campus confronted these challenges by participating in a year-long lesson study, a process of collaboratively planning,observing, and assessing a single lesson. By collectively identifying goals and priorities, designing and redesigning the lesson, and assessing outcomes through observation, surveys, and focus groups, librarians and teaching faculty negotiated varying expectations and demands for providing one-shot library instruction.
Keywords: First-year English; Library Instruction; Librarian-Faculty Collaboration; College and University Libraries; Freshmen; Lesson Study